Antibiotic use during pregnancy and asthma in preschool children: the influence of confounding. Issue 9 (13th June 2016) - Mulder, B.; Pouwels, K. B.; Schuiling‐Veninga, C. C. M.; Bos, H. J.; de Vries, T. W.; Jick, S. S.; Hak, E.
Summary: Background: A recent study suggested that early‐life intestinal microbiota may play an important role in the development of childhood asthma, indicating that antibiotics taken during early life or in late pregnancy may be associated with childhood asthma. Objective: This study aims to assess the association between prenatal antibiotic use and asthma in preschool children using data from the prescription database IADB.nl. To assess the influence of potential confounding, we conducted both a case–sibling and a case–control study and compared the results. Methods: We conducted a case–sibling study in which 1228 children with asthma were compared to 1228 siblings without asthma, using data from the prescription database IADB.nl. In addition, a case–control study was conducted. Asthma in preschool children was defined as ≥ 3 prescriptions for anti‐asthma medication within a year before the fifth birthday. Conditional logistic regression was used to estimate crude and adjusted odds ratios (aORs). Results: In both the case–sibling and case–control analysis, the use of antibiotics in the third trimester of pregnancy was associated with an increased risk of asthma in preschool children (aOR 1.37; 95% CI 1.02–1.83 and aOR 1.40; 95% CI 1.15–1.47). Time‐trend analyses showed that results were not influenced by a time trend in antibiotic exposure. A significant association between exposure to antibiotics in any trimester of pregnancy and the development of asthma in preschool children was observed in the case–control analysis only (aOR 1.46; 95% CI 1.34–1.59). Conclusion: Antibiotic use in the third trimester of pregnancy was associated with a small increased risk of asthma in preschool children. This association was robust to time‐invariant confounding or exposure time trends, further supporting the important role for early‐life intestinal microbiota in the development of childhood asthma.